Globalization’s Effects on the Value Base of the Finnish Core Curriculum : Perspectives of Cultural Heritage and Cultural Diversity - Lehtimäki, Maria; Lehtonen, Tommi (Society for Indian Philosophy and Religion, 2023)
Globalization and its effects on the society was one main motivation behind the reform of education from the Core Curriculum of 2004 to that of 2014. What traits characterize the Core Curriculum’s approach to globalization? To answer this question, we examine the Value Base of both the previous and the current document, paying attention to the shift between the Curricula. To map the traits, we adopt a two-fold understanding of globalization as something that both enriches and impoverishes cultures and create two perspectives (framings) that view globalization from these extremes. By equipping the hypothetical perspectives to a framing analysis of the value base, we find out, simply put, that the aim expressed in the value base has shifted from educating the learner on the diversity of the domestic culture to educating them on intercultural communication skills, paving the way to a supranational culture. While specific to the Finnish context, our examination and its results are relevant in the context of any national Core Curriculum. Globalization affects all learning cultures, one way or another, and it is highly important to be conscious of the stance taken to it on the level of education planning.
Keywords: Finnish school system; national curriculum; globalization; multiculturality; frame-sensitive reasoning; frames; value base; globalisation